SOCIAL ADAPTATION OF DISCHARGED MILITARY PERSONNEL - Tatyana A. Stakhy; Elena V. Li (Статистика и экономика, 2016)
In the life plans of servicemen, retired includevocational training or retraining, developmentof new relations, the formation of a new value system based on the new realities and theirsocial experience.The article considers legal and organizationalsupport of former soldiers, analyzed groupof servicemen discharged from the Armed Forces, as a speciﬁc social group and identiﬁed its place in the structure of Russiansociety; revealed the ways and forms ofadaptation to new conditions of life; to makean analysis of the life plans of servicemen,removed to the reserve.